Incorporating the UN Convention on the rights of the child into national law - Kilkelly, Ursula; Lundy, Laura; Byrne, Bronagh (Cambridge : Intersentia, 2021)
The United Nations Convention on the Rights of the Child (CRC) requires States Parties to take all appropriate measures to implement the rights in the Convention. As we celebrate the 30th anniversary of the Convention's adoption, focus has shifted onto the measures being taken at national level to give effect to children's rights with specific reference to legal incorporation both direct and indirect. The way in which the CRC is given legal effect is highly contingent upon the constitutional and legal systems of individual countries and can best be understood by those writing from the specific national context. So this book combines individual contributions that address the experience of legal incorporation in selected countries by their national experts, with comparative analysis of the international landscape from the world's leading authorities on legal implementation of the CRC. The result is an up-to-date, comparative and international analysis of the progress made around the world to incorporate the CRC, in the first comprehensive and analytical presentation of these issues. Incorporating the UN Convention on the Rights of the Child into National Law is a rich resource central to the work of every lawyer with an interest in the CRC or the incorporation of international legal instruments.
Title from publisher's bibliographic system (viewed on 10 Dec 2021).
Keywords: Convention on the Rights of the Child -- (1989 November 20); Children (International law); Children's rights